14C‐Dating Model for Groundwater Affected by CO2 Inputs From Deep Underground Formations. Issue 3 (10th March 2020) - Wang, Tao; Chen, Jiansheng; Zhang, Chenming; Zhan, Lucheng; Li, Ling
Abstract: Groundwater age, defined as the time since recharge, is useful for estimating groundwater renewal rates. Radiocarbon ( 14 C) activity has been widely applied for groundwater age dating since the 1950s. However, this approach can be complicated by other 14 C‐free carbon sources, which dilute the 14 C content at the time of groundwater recharge. Several corrective models have been introduced to determine the dilution factor using carbon isotopes and chemical mass balances, but these models do not account for the influence of deep crust and/or mantle (endogenic) carbon sources and are hence not applicable for dating groundwater affected by endogenic CO2 . Therefore, we developed a new 14 C groundwater dating model including three carbon end‐members (biogenically derived sedimentary carbon, carbonate carbon, and deep crust and/or mantle carbon) to quantify the dilution factor. This model was tested by age dating groundwater samples from the United States that were influenced by endogenic carbon (based on their δ 13 C value), showing that the conventional method overestimated the 14 C apparent age by 19% on average. The average uncertainty for the conventional and new method is approximately 1.58% and 11.2%, respectively. The new method proposed here can be applied to groundwater age dating in other regions where aquifers are influenced by endogenic CO2 . However, its application requires a priori identification of local geological, hydrogeological, and geochemical conditions. Key Points: A new 14 C groundwater dating method is proposed to account for the interference of CO2 inputs from deep crust and/or mantle sources The conventional 14 C apparent age is overestimated by 19% on average for groundwater samples that are influenced by endogenic CO2 The average uncertainty is approximately 1.58% and 11.2% for the conventional and new method, respectively